(untitled) (Journal of Economic Research & Business Administration, 2015)
This article describes the features of labor migration of Kyzylorda region. Migration processes affect the quality of labor, and hence on economic development in general. Therefore, migration processes, trends, factors causing migration, and the impact of migration on the labor market Kyzylorda region today are one of the most important aspects of the study. Analysis of the state of migration proves especially labor migration.